(untitled) (Journal of the College of Basic Education, 2022)
Fifteen Bacillus isolates originally isolated from soil surfaces were evaluated for possible antagonistic activity against some of molds included, Aspergillus, Penicillium, Fusarium and Rhizopus species. Five of the isolates (1, 3, 10, 13 and 15) possessed noticeable antagonistic properties, and were effective in suppressing the growth of previous mentioned pathogens. The maximum Inhibition (52.6%) against A. niger was noticed by isolate No: 15 at supernatant concentration of 35% v/v. The most active isolate named MHS15 identified by 16S rRNA gene sequencing as Bacillus subtilis (accuracy of 100%) which was matched with the sequence of B. subtilis OH2377A which recorded in Genebank under the Accession Number of gbIKF030229.1. Analysis of methanolic extract of B. subtilis MHS15 by RP-HPLC revealed that there were three isomers of iturin A at retention times of 3.025, 5.160 and 11.576 min which were conformable with the isomers formed from standard iturin A at the same retention times which were; 3.057, 5.178 and 11.753 min. Results obtained using the Electrospray ionization - Mass Spectrometry (ESI-MS) clarified that the three isomers of iturin A produced by B. subtilis MHS15 which had molecular weights of 1043.46, 1057.37 and 1071.48 Da respectively, reveals that they belong to iturin A2, A3 or A4 or A5 ( which have the same M.W.) and A6 or A7 (which have the same M.W.) respectively. All isomers produced by B. subtilis MHS15 were found to have an inhibitory action against to the growth of A. niger